DEVELOPMENT OF PEDAGOGICAL EDUCATION IN THE ROMANIAN REPUBLIC (Pedagogy of Higher and Secondary Education, 2008)
This article considers formation and development of the system of higher pedagogical education in romania as a member of Black sea economic cooperation.